(untitled) (Annals of Medical Research, 2021)
Aim: Meeting the family needs is one of the indicators of the quality of service provided in hospitals. The overlap between the needs and the perspective of the health workers will enable the needs to be met more quickly. Material and Methods: This study was conducted between 01.03.2019 and 01.06.2019 by using face-to-face interviews with the families whose relatives were being treated in the adult general intensive care unit (ICU) providing 26 beds in Ersin Arslan Training and Research Hospital and also with the doctors and nurses working in the same ICU. In the study, the family needs inventory, whose Turkish validity and reliability was approved, was used. The Turkish form of inventory consists of three subscales: “support and comfort need,” “proximity and safety need” and “information need”.Results: 311 family member and 68 health personnel participated in the study. The two of the first five most important family needs, is in the information need subscale, while the others are in the safety and proximity subscale class. All of the first five needs that health workers consider important are included in the safety and proximity subscale.Conclusion: The family needs and the identification of the needs by health care workers are largely overlapped. Awareness of the information subscale needs, should be raised.